Development of Android-Based Learning Media for Islamic Cultural History to Improve Students’ Learning Outcomes - Ramadhana Agung Pratama; Adi Fadli; Ismail Ismail; Wildan Wildan (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
The integration of digital technology in history education is still limited in many Islamic secondary schools, where learning is often dominated by text-based instruction that reduces student engagement and learning outcomes. This study aims to develop and evaluate Android-based learning media for Islamic Cultural History to improve student learning outcomes at Madrasah Aliyah Qamarul Huda Bagu. This research method uses a research and development (R&D) approach with the ADDIE model, followed by a quasi-experimental pre-test and post-test design to test the effectiveness of the learning. Data were collected through expert validation instruments, student response questionnaires, and achievement tests, and analyzed using descriptive statistics, normalized gain (N-gain), and comparative analysis of pre-test and post-test scores. The results indicate that the developed Android-based learning media is valid and practical, as confirmed by expert assessments and positive student responses. Furthermore, statistical analysis shows a significant increase in student learning outcomes after the media implementation, with the improvement in learning outcomes being in the moderate to high effectiveness category. These findings suggest that Android-based learning media can serve as an effective teaching tool that enhances conceptual understanding and active engagement in learning Islamic Cultural History.